Determination of sensory threshold limit of geosmin and 2-methylisoborneol for Filipino panellist and the reduction of these compounds in milkfish (chanos chanos) meat through acidification - Pahila, Jade Go (University of the Philippines Visayas, 2014)
A study on the reduction of off flavour compounds in milkfish (Chanos chanos through acidification and the determination of a human sensory detection threshold was conduced. The specific sensorial threshold levels of two common off-flavour compounds in water systems (geosmin and 2-methylisoborneol) were determined through a series od sensory evaluation tests. Two different threshold levels were obtained for both compounds in aqueous solutions : the absolute or detection threshold level and the terminal or saturation threshold level. Results of this study present specific threshold levels for each compound : geosmin had an absolute threshold level of 18 ng Li-1 and a terminal threshold level of 1700 ng Li-1, while 2-mythylisoborneol had absolute and terminal threshold levels at 14 ng Li-1 and 900 ng Li-1 respectively. Using the poled results of collective sensory responses of selected panellists, the detection and terminal threshold levels of 2-mythylisoborneol were found to be relatively lower as compared to that of geosmin. In addition,when the psychophysics law known as the Webner-Fechner model was used in the correlation of the results of the sensory tests, the sensry intensity perception responses of the panellists were found to follow a logarithmic function in relation to off-flavour compound concnetration as expressed in the equation : Intensity = m log (concentration) + b. Two independent studies on the acidification of milkfish meat for the removal of the presence followed with the acidification treatment, and the acidification of milkfish meat naturally contaminated with off-flavour. Subject compounds were processed using Solid Phase Microextraction method followed by quantification with GMCS. Two different food grade organic acids were used, 4% acetic acid and 1% citric acid. Acid concentrations were based on a previous study on the reduction of off-flavour compounds in water. Results of the spiking experiment showed a significant (P<0.05) increase in the concentration of geosmin but not in MIB. Acidification with acetic acid and citric acid of the spiked milkfish resulted to a significant decrease (P<0.05) of geosmin in both acid treatments, which accounts for more than 90% and 70% reduction respectively. Experiments on the acidification of milkfish meat naturally contaminated with off-flavours showed significant decrease (P<0.05) in the concentration of both geosmin and MIB for both acidification treatments. The citric-acidified treatments decreased the geosmin and MIB concentration from 0.1139 + 0.0322 ug Kg=1 to 0.0273 + 0.0139 ug Kg-1 and 0.2081 + 0.0247 ug Kg to 0.0769 + 0.0354 ug Kg respectively. Webner-fechner model application with the quantitative results of the acid treatments showed that the initial concentration of the compounds in the non-acidified samples scored halfway in the standard line scale used, and both acid treatments significantly dropped the sensory responses of both compounds. .An additional study on the effects of the acidification treatments in the moisture, protein and lipid content of the fish muscle was done. Results from this study showed that the soaking treatments significantly increased (P<0.05) the moisture content for both acid treatments. The protein content of the fish meat significantly decreased (P<0.05) only in the acetic acidified treatment ; and the lipid content of the fish sample significantly decreased (P<0.05) in both acid treatments. The changes in the composition of the fish muscles after the different acid treatments could be attributed to the change in pH of the system.